Impact of Hippotherapy on Gross Motor Function and Quality of Life in Children with Bilateral Cerebral Palsy: A Randomized Open-Label Crossover Study - Deutz, Ute; Heussen, Nicole; Weigt-Usinger, Katharina; Leiz, Steffen; Raabe, Christa; Polster, Tilman; Daniela, Steinbüchel; Moll, Christine; Lücke, Thomas; Krägeloh-Mann, Ingeborg; Hollmann, Helmut; Häusler, Martin (Neuropediatrics, 2018)
This study investigated the effect of hippotherapy on gross motor function (Gross Motor Function Measure [GMFM]-66, GMFM dimension E and D) and quality of life (Child Health Questionnaire [CHQ 28], KIDSCREEN-27 parental versions) in children with bilateral spastic cerebral palsy. Seventy-three children (age: 9.1 ± 3.3 years; male = 44; GMFCS levels II = 27; III = 17; IV = 29) were randomized to an early (n = 35) or late (n = 38) treatment group. Data from 66 probands were available for further analysis. Probands received hippotherapy once to twice weekly during a period of 16 to 20 weeks (mean: 17 treatments) in a crossover approach. Whereas no significant changes were found for total GMFM scores and quality of life parameters, a significant increase in GMFM dimension E was found. Children terminating the study early showed lower mean psychosocial quality of life scores than children who completed the whole study (CHQ-28 “psychosocial dimension”; KIDSCREEN-27 “mood and emotional dimension”). Our data are in line with previous reports and suggest that hippotherapy shows distinct therapeutic strengths with regard to promoting upright stand and gait in children with cerebral palsy. Children with higher psychosocial burden of disease may need special support to get access to and benefit from intensified physiotherapy programs.
Keywords: hippotherapy; gross motor function; cerebral palsy; quality of life; physiotherapy